1996
DOI: 10.4315/0362-028x-59.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Quality and Histamine Formation during Controlled Decomposition of Tuna (Thunnus thynnus)

Abstract: Histamine production was studied during controlled tunafish decomposition at 0, 8, and 20°C. The influence of the location of the anatomic section on the amount of histamine formed and the incidence of histidine decarboxylating bacteria were also considered. By the time of sensory rejection, histamine levels in tunafish sections stored at 0 and 20°C were still below the hazard levels and the allowable levels established by both the U.S. Food and Drug Administration (FDA) and the European Union. Toxic amounts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
53
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 0 publications
14
53
0
3
Order By: Relevance
“…Enterobacteriaceae increased from 2.0 x 10 2 on the 1st day to 6.5 x 10 9 cfu/g and that of Pseudomonas from 3.0 x 10 2 to 7.3 x 10 9 cfu/g by the 15 th day. These results are comparable to those reported for tuna by Lopez-Sabater et al (1995).…”
Section: Resultssupporting
confidence: 91%
“…Enterobacteriaceae increased from 2.0 x 10 2 on the 1st day to 6.5 x 10 9 cfu/g and that of Pseudomonas from 3.0 x 10 2 to 7.3 x 10 9 cfu/g by the 15 th day. These results are comparable to those reported for tuna by Lopez-Sabater et al (1995).…”
Section: Resultssupporting
confidence: 91%
“…Although standards or guidelines for permissible concentrations of histamine in fish products have not been established in Japan, the U.S. Food and Drug Administration sets the limit at 5 mg of histamine/100 g of muscle for scombroid fish (13). While many diverse analytical procedures have been published for histamine in unprocessed and canned fish (34), many studies (26,27,39) have shown that detectable amounts of histamine accumulated only after fish were completely decomposed or after aerobic plate counts reached Ͼ10 7 CFU/g in fish muscle. This was also confirmed in our study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While histamine in fermented products, such as wine (36), cheese (35,59), and fish sauce (31,57), is produced by gram-positive lactic acid bacteria, histamine in raw fish products is caused mostly by gram-negative enteric bacteria such as Morganella morganii, Klebsiella spp., and Enterobacter spp. (16,28,37,39). During the decomposition of fish such as tuna and mackerel, histamine forms in significant amounts due to bacterial decarboxylation of histidine present in the muscle tissue (69).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Colonies showing a purple halo with different morphological characteristics (form, elevation, color and halo intensity) were selected and inoculated into modified TSAH (tryptose-soycasein agar) medium supplemented with 0.1% of L-histidine at pH 7.0, in accordance with López-Sabater et al (1996a) and Du et al (2002).…”
Section: Isolation and Identification Of Histamine-forming Bacteriamentioning
confidence: 99%